PEMANFAATAN TEKNOLOGI MEDIA SOSIAL UNTUK KESADARAN DAN KEPEDULIAN MASYARAKAT TERHADAP COVID-19. - Ratna Mega Sari; Tintus Gustamal; Auvan Atthahara; Mohammad Rafli Fajriansyah; Syifa Fauziah Noer; Suci Nur Aulia; Lisdiana Nurfitriani (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
PEMANFAATAN TEKNOLOGI MEDIA SOSIAL UNTUK KESADARAN DAN KEPEDULIAN MASYARAKAT TERHADAP COVID-19. Ratna Mega Sari, Tintus Gustamal, Auvan Atthahara, Mohammad Rafli Fajriansyah, Syifa Fauziah Noer, Suci Nur Aulia, Lisdiana Nurfitriani Universitas Sultan Ageng Tirtayasa ratna.megasari@untirta.ac.id ABSTRACT Pondok Bahar village, Karang Tengah District is one of the villages that has been in the red zone for the spread of the corona virus. The low implementation of health protocols in the community and hoax information are the causes of the high spread of the virus in the area. Thus, this village has become the area chosen as a place for community service through online KKM activities at Sultan Ageng Tirtayasa University. The programs carried out in the KKM activity are divided into two main activities, namely the activity of providing correct information about covid 19 and socializing the prevention of covid 19 through social media in the form of poster and video content. The programs carried out include: Podcasts about preventing hoaxes about Covid-19 and vaccines, Creative Video Contest, making social media content in the form of posters related to covid 19 and making video content related to covid 19. Key words : Corona, Health protocol, KKM